Barriers to mental health help-seeking in veterinary professionals working in Australia and New Zealand: A preliminary cross-sectional analysis - Connolly, Caitlin Elizabeth; Norris, Kimberley; Dawkins, Sarah; Martin, Angela (Frontiers in Veterinary Science, 2022)
Despite higher reported rates of mental ill-health than the general population, professionals working in the animal care industry have low reported rates of help-seeking behaviour. Potential factors involved in veterinary professionals’ reluctance to seek help include stigma towards mental ill-health, practical barriers to accessing supports, and a cultural normalisation of symptoms in the industry. This preliminary study sought to explore these factors in a sample of veterinarians, veterinary nurses, and veterinary technicians and examine effects of gender, years’ experience, and practice location. A total of 408 veterinary professionals working in Australia and New Zealand completed an online survey between June and December 2021 measuring perceived stigma, practical barriers to mental health help-seeking, perceptions of normalised psychopathology and sickness presenteeism. Results indicated moderate levels of both perceived stigma and barriers to mental health help-seeking. Interestingly, psycho/pathology (e.g., burnout, fatigue, and sickness presenteeism) was perceived to be a normalised aspect of the profession by majority of respondents. Although no effect of gender or geographic location were observed, stage of career did have an effect on findings. Early career veterinary professionals were identified as more vulnerable to perceived stigma and barriers to care. The practical and research implications of the findings are discussed and include the need for mental health to be more centrally incorporated into the veterinary curriculum and professional development. Also discussed is an agenda for future research aimed at improving the mental health and wellbeing of professionals working in the animal care industry.